2013
DOI: 10.1016/j.biortech.2012.12.168
|View full text |Cite
|
Sign up to set email alerts
|

Improving effect of metal and oxide nanoparticles encapsulated in porous silica on fermentative biohydrogen production by Clostridium butyricum

Abstract: 12This paper investigated the enhancement effect of nanometre-sized metallic (Pd, Ag and Cu)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(61 citation statements)
references
References 35 publications
0
60
0
1
Order By: Relevance
“…In addition, the researchers have suggested that when the ambient temperature is relatively lower, bacteria need more ferrous ion to activate the hydrogenase enzyme, so that it can oxidize reduced ferredoxin for better production of molecular hydrogen [15]. Recently, metal oxide (Fe x O y ) nanoparticle has been applied to enhance fermentative hydrogen production due to its affinity for electrons and high reactivity [16,17]. However, it also faces a critical issue that hinders its application.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the researchers have suggested that when the ambient temperature is relatively lower, bacteria need more ferrous ion to activate the hydrogenase enzyme, so that it can oxidize reduced ferredoxin for better production of molecular hydrogen [15]. Recently, metal oxide (Fe x O y ) nanoparticle has been applied to enhance fermentative hydrogen production due to its affinity for electrons and high reactivity [16,17]. However, it also faces a critical issue that hinders its application.…”
Section: Introductionmentioning
confidence: 99%
“…The increased surface area provided by HT nanoparticles and their action as biocatalysts leads to enhancement of microorganism activity and possible enhanced bacterial anchoring. This in turn, may be the cause of greater microbial growth in samples with HT addition (Rodriguez-Chiang et al, 2016;Beckers et al, 2013).…”
Section: Effect Of Hydrotalcite Additionmentioning
confidence: 95%
“…It was observed that microbial growth was higher in all samples containing HT compared to the samples with no HT addition. Studies have found that some microorganisms take advantage of nanoparticles, especially in anaerobic conditions, by transferring more efficiently electrons to acceptors (Beckers et al, 2013). The increased surface area provided by HT nanoparticles and their action as biocatalysts leads to enhancement of microorganism activity and possible enhanced bacterial anchoring.…”
Section: Effect Of Hydrotalcite Additionmentioning
confidence: 99%
“…Clostridium butyricum fue el primer microorganismo electrogénico Gram positivo (Beckers et al, 2013), un tipo de bacteria anaeróbica estricta, que puede producir electricidad metabolizando almidón, sacarosa y otros polisacáridos. Clostridium beijerinckii también puede producir electricidad usando almidón, melaza, glucosa y ácido láctico (Zhang et al, 2013).…”
Section: Biopelículasunclassified